PENGARUH KUALITAS PELAYANAN KLINIK GIGI TERHADAP KEPUASAN DAN KEPERCAYAAN PASIEN SEHINGGA MENINGKATKAN KEINGINAN UNTUK BEROBAT KEMBALI - Pratama Kesuma Tanudjaya (Jurnal Manajemen dan Pemasaran Jasa, 2014)
The background of this research was due to intense competition, the management of dental clinic seeks to attract patients by providing excellent quality of service.The objective of this research wasto analyze whether the quality of services provided from a dental clinic can rise the desire of patients to seek treatment again.The design of this research applies a survey. The type of investigation was casuality. Total sample researched was 201 dental patients. The result of this research conclude thatamong the three factors studied, patients trust have the most influence on patient intention for treatment again.Key words: Service quality, costumer’s satisfaction, trust, intention to come.